An insight into asphaltene precipitation, deposition and management stratagems in petroleum industry - Adebiyi, Festus M. (Journal of Pipeline Science and Engineering, 2021)
Petroleum industry is the mainstay of the economical enlargement of many nations. Most of the market prices of all commodities are built on the cost of wide-range of petroleum products. Prompt identifying and alleviating challenges facing this sector can reduce costs and enhance productivity and economic growths. Asphaltene deposition, a crucial operational challenge in some petroleum production facilities is one of the key challenges facing petroleum sector universally. Asphaltene clogs pipelines as cholesterols block blood vessels; this has made asphaltene deposition management a principal factor to consider before establishing any petroleum producing company. Therefore, in order to guarantee urbane and uninterrupted movement of petroleum to the consumers, it is vital for the field Operators, Engineers and Chemist to be pipeline deposition conscious as lines would suffer degradation owing to asphaltene precipitation, aggregation and eventual deposition. There are documented literatures on asphaltene, but almost new information is disseminated in literature or occurs in the brains of experts comparable to silent knowledge. The mission of this review paper is to publicize the information and close some knowledge-breaks. This particular article provides an inclusive appraisal of asphaltene interaction, precipitation, deposition, challenges and management stratagems. Besides, it provides a conclusion and prised recommendations.